2020
DOI: 10.3390/ijms21228601
|View full text |Cite
|
Sign up to set email alerts
|

In-Silico Identified New Natural Sortase A Inhibitors Disrupt S. aureus Biofilm Formation

Abstract: Sortase A (SrtA) is a membrane-associated enzyme that anchors surface-exposed proteins to the cell wall envelope of Gram-positive bacteria such as Staphylococcus aureus. As SrtA is essential for Gram-positive bacterial pathogenesis but dispensable for microbial growth or viability, SrtA is considered a favorable target for the enhancement of novel anti-infective drugs that aim to interfere with key bacterial virulence mechanisms, such as biofilm formation, without developing drug resistance. Here, we used virt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…Skyrin, a bisanthraquinone compound derived of two emodin (6-methyl-1,3,8-trihydroxyanthraquinone) moieties connected by a single C–C bond ( Figure 6 ), exhibited Sa-SrtA inhibitory effects with IC 50 values in the range of 24–31 µM. The anti-virulence potential is unfortunately reduced by the strong growth inhibitory activity against S. aureus Newman strain (MIC values around 10 µM) [ 69 ]. Emodin had little effect on Sa-SrtA at 100 µM [ 28 ].…”
Section: Sortase a Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Skyrin, a bisanthraquinone compound derived of two emodin (6-methyl-1,3,8-trihydroxyanthraquinone) moieties connected by a single C–C bond ( Figure 6 ), exhibited Sa-SrtA inhibitory effects with IC 50 values in the range of 24–31 µM. The anti-virulence potential is unfortunately reduced by the strong growth inhibitory activity against S. aureus Newman strain (MIC values around 10 µM) [ 69 ]. Emodin had little effect on Sa-SrtA at 100 µM [ 28 ].…”
Section: Sortase a Inhibitorsmentioning
confidence: 99%
“…Four synthetic derivatives were tested on Sa-SrtA and showed IC 50 values in the range of 130–160 µM and strongly disrupted staphylococcal biofilm formation [ 79 ]. The structurally related compound, (4,5-dichloro-1 H -pyrrol-2-yl)-[2,4-dihydroxy-3-(4-methyl-pentyl)-phenyl]-methanone ( Figure 8 ), produced Sa-SrtA (IC 50 = 47 µM) inhibition along with a reduction in biofilm formation, but demonstrated also potent anti-staphylococcal activity [ 69 ].…”
Section: Sortase a Inhibitorsmentioning
confidence: 99%
“…Although initial hits can be generated by each of the approaches individually, these approaches complement each other well, and, thus, combining them in a single study could yield better results. While working on this article and exploring the repertoire of uncovered sortase inhibitor leads (extensively summarized in Supplementary Material Table S1 [ 84 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ]), we observed that despite the great advances in this field, there was also a great ambiguity in the acquired results.…”
Section: Srta Inhibitorsmentioning
confidence: 99%
“…Despite their starting point, all injuries may transmitted by microorganisms or outside bodies or both to another area. Anaerobic microorganisms forms, 33% of the accumulated number of microbial species in colonized injuries, and their number increments increases to around half-in contaminated injuries [4][5][6][7]. Microbe of Pseudomonas aeruginosa could be one of the most causative agent for post-surgery wound infections, also the nosocomial infection which caused by multi-drug resistant, in the United [10].…”
Section: Introductionmentioning
confidence: 99%